2013
DOI: 10.1007/s00234-013-1229-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion diffusion-weighted MR imaging of gliomas: feasibility of the method and initial results

Abstract: The IVIM-fitted post-processing of DWI-signal decay in human gliomas could show significantly different values of fractional perfusion-related volume and fast diffusion coefficient between low- and high-grade tumors, which might enable a noninvasive WHO grading in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
89
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 27 publications
20
89
7
Order By: Relevance
“…We have shown that our CVs with smoothing (ie, full width at half maximum ϭ 3 mm) were generally 3 times lower than when no smoothing was applied. When one assesses CVs with no smoothing (f, CV Յ 12.20%; and D, CV Յ 2.34%), it can be observed that CVs are in the same range as in the other studies (ie, f, 5.8%-11.1%; and D, 0.6%-2.1% 12,15,14 ). This finding indicates that the reproducibility of IR-IVIM is like that of conventional IVIM.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We have shown that our CVs with smoothing (ie, full width at half maximum ϭ 3 mm) were generally 3 times lower than when no smoothing was applied. When one assesses CVs with no smoothing (f, CV Յ 12.20%; and D, CV Յ 2.34%), it can be observed that CVs are in the same range as in the other studies (ie, f, 5.8%-11.1%; and D, 0.6%-2.1% 12,15,14 ). This finding indicates that the reproducibility of IR-IVIM is like that of conventional IVIM.…”
Section: Discussionsupporting
confidence: 62%
“…Several groups have investigated the reproducibility of conventional IVIM and have shown good results (eg, low coefficients of variation [CVs]) for both the perfusion volume fraction and parenchymal diffusivity. [12][13][14][15] Thus far, only 1 reproducibility study has been performed on IR-IVIM. This study examined only f and healthy participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Previous reports found that the second approach delivered the most robust and signal-to-noise-enhanced results; therefore, IVIM parameters were calculated by using the second approach in all patients. 7,8 In addition, an ADC measurement was calculated by using bϭ0 and 900 s/mm 2 and a simple monoexponential fit to compare the ADC with the IVIM-derived D.…”
Section: Ivim Fittingmentioning
confidence: 99%
“…IVIM also demonstrated sensitivity in measuring changes in cerebral blood flow under suppression of extravascular water signals in an experimental setting in a rat brain [3]. Recently, the bi-exponential behavior of signal decay in brain tumours was demonstrated, and its clinical application may include tumour grading [4,5] and differentiation of recurrent tumours from post-treatment effects [6].…”
Section: Introductionmentioning
confidence: 97%